2019
DOI: 10.1021/acscatal.9b02936
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Concerted Proton-Coupled Electron Transfer during Oxygen Evolution on Hematite Using Lanthanum Oxide as a Solid Proton Acceptor

Abstract: The utilization of a support material has been an effective method for the management of proton transfer on catalytic active centers. Previous studies showed that the large overpotential of α-Fe2O3 for the oxygen evolution reaction (OER) resulted from the sequential transfer of electrons and protons. Here, by combining α-Fe2O3 with La2O3, which functions as a solid proton acceptor, concerted proton–electron transfer (CPET) was induced. The induction of CPET facilitated the formation of intermediate species, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…For example, She et al 17 reported that by introducing proton acceptor Sr 3 B 2 O 6 into various perovskite-based oxides, including LaCoO 3−δ , La 0.4 Sr 0.6 CoO 3−δ , Pr 0.5 Ba 0.5 CoO 3−δ , Ba 0.5 Sr 0.5 Co 0.8 FeO 3−δ , and Sr 0.8 Co 0.8 Fe 0.2 O 3−δ , OER activities can be significantly improved, which is attributed to the facilitated deprotonation process. Similar effects in promoting proton transfer and corresponding OER activity were observed by Takashima et al 18 when they introduced solid proton acceptor La 2 O 3 into α-Fe 2 O 3 . These pioneering studies suggest that it is possible to tune the PCET process and improve the OER activity by regulating the proton transport properties in materials.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…For example, She et al 17 reported that by introducing proton acceptor Sr 3 B 2 O 6 into various perovskite-based oxides, including LaCoO 3−δ , La 0.4 Sr 0.6 CoO 3−δ , Pr 0.5 Ba 0.5 CoO 3−δ , Ba 0.5 Sr 0.5 Co 0.8 FeO 3−δ , and Sr 0.8 Co 0.8 Fe 0.2 O 3−δ , OER activities can be significantly improved, which is attributed to the facilitated deprotonation process. Similar effects in promoting proton transfer and corresponding OER activity were observed by Takashima et al 18 when they introduced solid proton acceptor La 2 O 3 into α-Fe 2 O 3 . These pioneering studies suggest that it is possible to tune the PCET process and improve the OER activity by regulating the proton transport properties in materials.…”
supporting
confidence: 78%
“…Therefore, its careful rationalization may be imperative to fully understand the mechanism. As mentioned in the introduction section, a number of recent works reported that by introducing a proton acceptor in the bulk materials, the deprotonation process can be strongly facilitated, resulting in improved OER activities 17,18 . To further understand the mechanism for the difference in OER activity of PBSCF thin films, the ionic diffusion characteristics in the PBSCF thin films were experimentally taken into account.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using the Pt electrocatalyst reported a HER overpotential as large as >250 mV at −4 mA cm −2 in solutions of 0.1 M Na 2 SO 4 [16] and 0.1 M KClO 4 [17] at pH 7.0, which is substantially larger than 30 mV at pH 13 in the solutions of 0.1 M NaOH [16] and 0.1 M KOH [17] . Similarly, the OER overpotential at 0.1 mA cm −2 of α‐Fe 2 O 3 in 0.1 M Na 2 SO 4 at pH 7.0 was >700 mV, while that in 0.1 M NaOH at pH 13 was below 450 mV [18] . This poor performance reported at the near‐neutral pH to those under extreme pH conditions called for research activity in this direction.…”
Section: Introductionmentioning
confidence: 89%
“…[17] Similarly, the OER overpotential at 0.1 mA cm À 2 of α-Fe 2 O 3 in 0.1 M Na 2 SO 4 at pH 7.0 was > 700 mV, while that in 0.1 M NaOH at pH 13 was below 450 mV. [18] This poor performance reported at the nearneutral pH to those under extreme pH conditions called for research activity in this direction.…”
Section: Introductionmentioning
confidence: 99%